Экономико-математическая модель эффективного управления в туристической отрасли - Падерин, А.В. (Культура народов Причерноморья, 2013)
В статье рассматриваются факторы, влияющие на спрос в туристической отрасли и
взаимосвязи между этими факторами. Кроме того, уделяется внимание аспектам, формирующим
потребительский выбор с позиции полезности. На основании рассмотренных вышеперечисленных
взаимосвязей определяются направления работы государства в сфере туризма. У статті розглядаються чинники, що впливають на попит в туристичній галузі і
взаємозв'язку між цими чинниками. Крім того, приділяється увага аспектам, що формують споживчий
вибір з позиції корисності. На підставі розглянутих вищеперелічених взаємозв'язків визначаються
напрями роботи держави у сфері туризму. The factors, influencing on demand in tourist industry, and the intercommunication between them,
are examined in the article. Thus the author comes from that demand is an amount of commodity or services,
which will be purchased at certain price for certain period of time. Therefore as it applies to the sphere of
tourism the question is about intercommunication between the amount of tourists and the average cost of 1 bed
per day in hotels, between the amount of recreants and the average cost of 1 bed per day in health–resorts. At
the same time the average cost of 1 bed per day depends on the tourists incomes, their amount, quality of hotel
and health–resort services. The major factor among mentioned above are tourists incomes which determine the
amount of tourists and quality provided services. Except price the demand is influenced by such factors, as state
expenses on tourist industry advancement, level of corruption, situation with public investments in the tourism
sphere, exchange rate. However, information on these indexes is discrete, that does not allow to estimate their
influence on demand. In addition, attention to the aspects, forming a consumer choice from the position of utility,
is also payed to. On the basis of the considered above intercommunications the fields of state work in the sphere
of tourism are determined.